Pengaruh Komposisi Campuran Minyak Sereh Wangi dan Minyak Cengkeh terhadap Unjuk Kerja Mesin Diesel - Rico Aditia Prahmana; Devia Gahana Cindi Alfian; Didik Supriyadi; Dicky Januarizky Silitonga; Abdul Muhyi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
The increase in fuel prices makes the use of essential oils as a natural bio-additive in diesel engines much in demand. This is because essential oils are believed to have good content to improve engine performance and reduce fuel consumption. In this research, essential oils used are citronella oil because they contain carboxylic compounds (-COOH) and clove oil which has the advantage to prevent corrosion. The aim is to improve engine performance and reduce fuel consumption can also prevent corrosion. This research was conducted by mixing citronella oil and clove oil with diesel fuel with a percentage of 1%, 0.5%, and 0.1% of the total volume. The diesel engine is operated with a loading variation of 200, 400, 600, 800, 1000, 1200, 1400, 1600, 1800, and 2000 W at a constant engine speed of 1500 rpm. The variables measured and calculated in this experiment are power, torque, Brake Mean Effective Pressure (BMEP), Specific Fuel Consumption (SFC). The results showed that the addition of citronella oil and clove oil to diesel fuel with a percentage of 0.1%, 0.5%, and 1% significantly reduced fuel consumption by 14.6%, 12.9%, and 18.3%, respectively. The maximum fuel reduction from mixed oils is only 0.086 liters/hour at 1000W loads with 1% bio-additives content.